Edukasi dan Demonstrasi Memasak Puding Labu Kuning Sebagai Alternatif Makanan Sehat Untuk Penderita Hipertensi Dusun I Desa Ranteleda - Suaib, Suaib; Apriyanti, Apriyanti; Pawah, Muhamad Aziz M; Rahman, Widya Fauzia; Tulas, Prisly Ananda; Mako, Yulviana Prastika; Raokang, Mutia Ahsun; Susanti, Riska Aulia; Lisa, Debora; Rifno, Rifno; Delviani, Ni Made (Abdimas Indonesian Journal, 2024)
Hypertension or high blood pressure is a condition where the systolic blood pressure exceeds 140 mmHg and the diastolic blood pressure exceeds 90 mmHg after two measurements at a five-minute interval while at rest. Around 972 million people worldwide suffer from hypertension, and this figure is expected to increase to 1.5 billion people by 2025. One important approach to managing hypertension is through a healthy diet. Pumpkin, which is rich in fiber, vitamins and minerals, has been shown to have benefits in lowering blood pressure, making it a good alternative for consumption by hypertension sufferers. This community service activity aims to provide education about hypertension and demonstrate how to cook pumpkin pudding as a healthy food for hypertension sufferers in Hamlet I, Ranteleda Village. Education is provided in the form of lectures and distribution of leaflets, while cooking demonstrations teach how to prepare healthy food using local ingredients that are low in salt and fat. The results of this activity showed an increase in participants' knowledge about hypertension and the importance of healthy eating patterns. This activity ran smoothly and effectively, and had a positive impact in increasing public awareness about the importance of managing hypertension through a healthy diet.